Scalable perovskite/CIGS thin-film solar module with power conversion efficiency of 17.8%. Issue 20 (10th May 2017) - Paetzold, U. W.; Jaysankar, M.; Gehlhaar, R.; Ahlswede, E.; Paetel, S.; Qiu, W.; Bastos, J.; Rakocevic, L.; Richards, B. S.; Aernouts, T.; Powalla, M.; Poortmans, J.
Abstract : All-thin film perovskite/CIGS multijunction solar modules, combining a semi-transparent perovskite top solar module stacked on a CIGS bottom solar module, are a promising route to surpass the efficiency limits of single-junction thin-film solar modules. Abstract : All-thin film perovskite/CIGS multijunction solar modules, combining a semi-transparent perovskite top solar module stacked on a CIGS bottom solar module, are a promising route to surpass the efficiency limits of single-junction thin-film solar modules. In this work, we present a scalable thin-film perovskite/CIGS photovoltaic module with an area of 3.76 cm 2 and a power conversion efficiency of 17.8%. Our prototype outperforms both the record single-junction perovskite solar module of the same area as well as the reference CIGS solar module. The presented perovskite/CIGS thin-film multijunction solar module makes use of the "4-terminal architecture", which stacks the perovskite solar module in superstrate configuration on top of the CIGS solar module in substrate configuration. Both submodules apply a scalable interconnection scheme that can accommodate scale-up towards square meter scale thin-film multijunction solar modules. In order to identify the future potential of the presented stacked perovskite/CIGS thin-film solar module, we quantify the various losses in the presented prototype and identify the key challenges of this technology towards very high power conversion efficiencies.